Biomechanical efficacy of collagen crosslinking in porcine cornea using a femtosecond laser pocket - Wollensak, Gregor; Hammer, Christian Manfred; Spörl, Eberhard; Klenke, Jörg; Skerl, Katrin; Zhang, Yao; Sel, Saadettin (Cornea, 2014)
Purpose: - The aim of this study was to assess the biomechanical efficacy of transepithelial collagen crosslinking using the femtosecond laser pocket technique compared with that using the standard crosslinking (CXL) technique. - Methods: Forty ex vivo porcine eyes were divided into 4 groups with 10 samples each. Group 1 comprised the untreated controls. Group 2 was the standard CXL group with debridement, instillation of 0.1% riboflavin-dextran solution for 15 minutes before and every 5 minutes during the 30 minutes of irradiation with ultraviolet A (UVA) light of 370 nm and an irradiance of 3 mW/cm². Group 3 pertained to the femtolaser pocket control with an intrastromal pocket but without riboflavin/UVA. Group 4 was the femtolaser pocket CXL group with an intrastromal pocket of an 8-mm diameter at a 180-μm depth, riboflavin/dextran application for 15 minutes and subsequent exposure to UVA light for 30 minutes. Postoperatively, biomechanical stress-strain measurements were performed. - Results: In the standard CXL group, the stress at 10% strain was 207.8 ± 64.1 × 103 Pa (+79.45% vs. controls; P = 0.021) compared with 115.8 ± 20.8 × 103 Pa in the untreated control group; in the crosslinked femtolaser pocket group, it was 159.5 ± 30.4 × 103 Pa (+37.74%; P = 0.049), in the non-cross-linked femtolaser pocket group, it was 103.5 ± 17.3 × 103 Pa (−10.62%; P = 0.103). The Young modulus was 5.4 MPa (+100% vs. controls) in the standard CXL group, 3.7 MPa (+37.04%) in the crosslinked femtolaser pocket group, and 2.4 MPa (−11.12%) in the non-cross-linked femtolaser pocket group compared with 2.7 MPa in the untreated control group. - Conclusions: The biomechanical effect of CXL using the femtolaser pocket technique is about 50% less pronounced than that after standard CXL. Future studies will show whether the efficacy of the technique can still be improved and whether the clinical effect is sufficient for stabilizing ectatic corneas.